All-optical processing technologies for next generation optical networks - Wang, Dawei (2012)
All-optical processing technologies are highly desirable for next generation optical networks because they can resolve the electrical bottleneck issues. All-optical processing technologies span many research areas, which include optical buffering, optical logic gates, optical wavelength conversion/multicasting, optical signal regeneration, ultra-fast optical switching, optical signal modulation format conversion, de-multiplexing of optical time division multiplexing (OTDM) signal, optical data exchange, and etc. This thesis focuses on two aspects of all-optical processing technologies; namely, optical buffering and wavelength multicasting.